2022
DOI: 10.1007/s13178-022-00767-y
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults’ Understanding of Sexual Competence: A Qualitative Study with German University Students

Abstract: Introduction Handling sexual interactions in a competent manner is a key skill for young adults, which is linked to positive aspects of sexual and general well-being. Several research conceptualizations of sexual competence have been proposed in the literature, but little is known about how young adults define sexual competence and what consequences they consider low sexual competence may have. Methods In this qualitative study conducted in 2019, 571 unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…51,52 Moreover, recent research on sexual behavior, especially with college students, has shown that the aspects defining risky sexual behavior for the purposes of this study, such as alcohol use, casual sex, and ambiguous communication in sexual interactions, remain prominent in young adults' sexual interactions. 21,53 Finally, there is little evidence of a decrease in rape myth acceptance and victim-blaming after the start of the #MeToo movement. 54,55 Therefore, we believe our findings may contribute to a better understanding of risk factors of men's and women's perpetration of sexual aggression in the current research landscape and societal debate.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Moreover, recent research on sexual behavior, especially with college students, has shown that the aspects defining risky sexual behavior for the purposes of this study, such as alcohol use, casual sex, and ambiguous communication in sexual interactions, remain prominent in young adults' sexual interactions. 21,53 Finally, there is little evidence of a decrease in rape myth acceptance and victim-blaming after the start of the #MeToo movement. 54,55 Therefore, we believe our findings may contribute to a better understanding of risk factors of men's and women's perpetration of sexual aggression in the current research landscape and societal debate.…”
Section: Discussionmentioning
confidence: 99%
“…How does sexual competence show itself?” and (2) “How does low sexual competence manifest? What consequences may low sexual competence have?” They were asked to give free responses without any length restrictions, which were content-analyzed as presented elsewhere (Tomaszewska et al, 2022a).…”
mentioning
confidence: 99%